A selection of relevant Portuguese children's literature published in the period of World War I - Reis da Silva, Sara (2019)
The systemic singularities of children’s literature seem to have determined the relative inconsistency of critical approaches based on historiography, where the “nodal points” are mainly of a temporal, topographical, institutional and figurative nature. One of the historical periods whose “historiographical reading” of literary outlines is incomplete and unsystematised corresponds to the timeframe between the beginning and the end of World War I. We will revisit some Portuguese authors and their works: O Navio dos Brinquedos [The Toy Ship] (1914) by António Sérgio, Era uma Vez[Once Upon a Time] (1916) by Maria Sofia Santo Tirso, and the “Polichinelo” [Punchinello] series (1918–1921) by Emília de Sousa Costa, published between 1914 and 1918, in an attempt to elucidate their technical singularities, and their most relevant ideothematic lines. Falling under the category of First Republic literature, these texts betray aesthetic sensibilities and very different ideologies, showing what was written for children and what young readers read in wartime.
Sustavne posebnosti dječje književnosti kao da su odredile relativnu nedosljednost kritičkih pristupa temeljenih na historiografiji, gdje su „čvorišne točke“ uglavnom vremenske, topografske, institucionalne i figurativne prirode. Jedno od povijesnih razdoblja čije je „historiografsko čitanje“ književnih obrisa nepotpuno i nesustavno odnosi se na vremenski okvir Prvoga svjetskoga rata. Osvrnut ćemo se na određene portugalske pisce i njihova djela objavljena između 1914. i 1918., konkretno na O Navio dos Brinquedos [Brod igračaka] (1914) Antónija Sérgija, Era uma Vez [Jednom davno] (1916) Marie Sofije Santo Tirso, te nakladnički niz „Polichinelo” [Pulčinelo] (1918. – 1921.) Emílije de Sousa Costa, kako bismo razjasnili njihove izražajne posebnosti i najvažnija ideotematska obilježja. Iako navedeni tekstovi pripadaju književnosti Prve Republike, odaju razne estetske senzibilitete i izrazito različite ideologije, pokazujući što se u ratno doba pisalo za djecu i što su mladi čitatelji čitali.
Die systemischen Besonderheiten der Kinder- und Jugendliteratur scheinen die relative Unstimmigkeit der auf Historiographie basierenden kritischen Ansätze bestimmt zu haben, wobei die „Schwingungsknoten“ meist temporaler, topographischer, institutioneller und figurativer Natur sind. Eine solche geschichtliche Periode deren „historiographische Leseart“ der literarischen Umrisse unvollständig und unsystematisch ist, entspricht dem Zeitraum vom Beginn bis zum Ende des Ersten Weltkriegs. Wir werden bestimmte portugiesische Autoren und deren Werke, die zwischen 1914 und 1918 herausgegeben wurden, wiederaufgreifen und zwar: O Navio dos Brinquedos [Das Spielzeugschiff] (1914) von António Sérgio, Era uma Vez [Es war einmal] (1916) von Maria Sofia Santo Tirso, sowie die Bände „Polichinelo” [Pulchinello] (1918 – 1921) von Emília de Sousa Costa, um die Besonderheiten in deren Ausdrucksweise, sowie deren wichtigste ideologisch-thematischen Eigenschaften zu klären. Auch wenn die hier genannten Texte der Literatur der Ersten Republik gehören, lassen sich darin bestimmte ästhetische Sensibilitäten und sich stark unterscheidende Ideologien erkennen, woraus ersichtlich wird, was in der Kriegszeit für Kinder geschrieben wurde und was junge Leser gelesen haben.
Bibliografske bilješke uz tekst ; bibliografija: str. 257-258.
Summary ; Sažetak ; Zusammenfassung.
Keywords: Portugalska književnost -- Dječja književnost -- Povijest književnosti -- Prvi svjetski rat